การศึกษาเชิงทดลองคลื่นความดันหนึ่งลูกในระบบท่อกรณีติดตั้งหม้อพักชนิดสะท้อนเสียง - ขันติโกมล ปรีชา; ญาติฉิมพลี สมภพ; พลสงคราม ไมตรี; อภิสิทธิ์ภิญโญ วิวัฒน์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2014)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาเชิงทดลองคลื่นความดันหนึ่งลูกในระบบท่อ กรณีติดตั้งหม้อพักชนิดสะท้อนเสียง ในการศึกษานี้ใช้อุปกรณ์กำเนิดคลื่นความดันแบบหนึ่งลูกขนาดความจุ 625 cm3 ซึ่งจำลองเท่ากับปริมาตรหนึ่งกระบอกสูบของเครื่องยนต์ดีเซลสี่สูบความจุ 2500 cm3 ควบคุมการเปิดปิดวาล์วกระบอกสูบด้วยชุดนิวแมติกส์ ใช้ท่อตรงทองเหลืองเส้นผ่าศูนย์กลาง 43 mm ยาว 6 m กรณีติดตั้งหม้อพักไอเสียชนิดสะท้อนคลื่นเสียงจะติดตั้ง ณ ตำแหน่ง 1/2 ของความยาวท่อ ทำการวัดความดันสถิต ณ ตำแหน่งห่างจากกระบอกสูบ 0.1 m, 2.5 m และ 5.9 m สำหรับกรณีท่อตรงและสำหรับกรณีติดตั้งหม้อพัก จะทำการวัดความดันตำแหน่งห่างจากกระบอกสูบ 0.1 m ตำแหน่งหน้าหม้อพัก 0.5 m หลังออกจากหม้อพัก 2 m และตำแหน่งปลายท่อ 1 m ผลการศึกษาแสดงให้เห็นว่า ความดันเมื่อออกจากอุปกรณ์กำเนิดคลื่นความดันแบบหนึ่งลูกเข้าสู่ระบบท่อ จะมีค่าความดันลดลงอย่างมาก แต่อย่างไรก็ตาม ยังมีค่าสูงกว่าความดันบรรยากาศ ขนาดแอมปลิจูดของคลื่นความดันจะลดลงตามความยาวของทอ่ เนื่องจากผลของความเสียดทาน เมื่อคลื่นเคลื่อนที่ถึงปลายทอ่จะมีการสะทอ้ นความดันยอ้ นกลับที่มีคา่ ต่ำกวา่ บรรยากาศหรือกลับเฟส เมื่อติดตั้งหมอ้ พักชนิดสะทอ้ นเสียงจะมีการสะท้อนคลื่นจากหม้อพักในลักษณะกลับเฟสเสมือนปลายท่อเปิด และมีจำนวนลูกคลื่นเพิ่มเป็นสองเท่าของกรณีที่ไม่ติดตั้งหม้อพัก เห็นชัดเจนว่าคลื่นความดันเมื่อเคลื่อนที่ผ่านหม้อพักจะยังคงมีเฟสเช่นเดิม แต่มีขนาดแอมปลิจูดลดลงอย่างมาก และจะมีการสิ้นสูญอย่างรวดเร็วจากการสะท้อนเพียงไม่กี่ครั้ง คำสำคัญ : คลื่นความดัน; ระบบท่อ; หม้อพัก; ความดันสถิต Abstract This research aims to experimentally study the pressure wave in pipe system installing a reflective silencer. In the present study, the single pulse pressure wave generator with volume 625 cm3 that is the same as a cylinder volume of 2500 cm3 four strokes diesel engine have been prepared. The pneumatic system has been employed to control the valve. The 43 mm inner diameter brass with 6 m length was tested. In the case of installing reflective silencer, it was placed at center of the pipe. Several pressure sensors were employed to measure the real time static pressure at the positions 0.1, 2.5 and 5.9 m from the pressure wave generator for the pipe without the reflective silencer. In the case with the reflective silencer, the static pressures were measured at position 0.1 from the cylinder, 0.5m in front of the silencer, 2 m after the silencer and 1 m from the end. The results indicated that there were extremely pressure drop across the valve but it was higher than the atmospheric pressure. The amplitude of pressure wave gradually decreases along the pipe due to the effect of friction. When the pressure wave propagates to the open end of the pipe, the pressure wave was reflected with phase change that is vacuum pressure. The installing reflective silencer affects to the reflection of pressure wave, which have the phase change as the open end. There were double pressure waves occur in pipe at the upstream side. Obviously, the phase of the throughout pressure wave across the reflective silencer did not change but the amplitude extremely decrease. The pressure wave was rapidly vanished in a few reflection times. Keywords : Pressure wave; Pipe system; Silencer; Static pressure